Effect of Low-Dose Hydrocortisone Therapy in Adult Patients With Septic Shock: A Meta-Analysis With Trial Sequential Analysis of Randomized Controlled Trials. (October 2020) - Lyu, Qing-Quan; Chen, Qi-Hong; Zheng, Rui-Qiang; Yu, Jiang-Quan; Gu, Xiao-Hua
Background: The efficacy of low-dose hydrocortisone therapy in the management of septic shock remains controversial in critical care for many years. Hence, we performed this meta-analysis of randomized controlled trials (RCTs) with trial sequential analysis (TSA) to evaluate its effect on clinical outcome among adult patients with septic shock. Methods: We identified relevant RCTs published from inception to March 7, 2018 comparing low-dose hydrocortisone with placebo or no intervention in adults admitted to the intensive care unit (ICU) for septic shock. Meta-analyses were performed for the primary and secondary outcomes. The risk of bias was assessed using the Cochrane Collaboration's instrument. Trial sequential analysis was used to pool the results from the included studies for the primary outcomes. Results: Thirteen studies were retrieved by our literature search strategy. There were no significant differences in 28-day mortality (odds ratio [OR] = 0.90, 95% confidence interval [CI] = 0.81-1.00; P = .05) and hospital mortality (OR = 0.91, 95% CI = 0.82-1.02; P = .09) between the 2 groups, which were confirmed by TSA. However, there was a significant improvement in shock reversal in the hydrocortisone group (OR = 1.33, 95% CI = 1.02-1.72; P = .03). Furthermore, subgroup analyses revealed that hydrocortisone plus fludrocortisone statistically reduced the rate of 28-day mortality (OR = 0.79, 95% CI = 0.64-0.97; P = .03), ICU mortality (OR = 0.77, 95% CI = 0.63-0.95; P = .02), and hospital mortality (OR = 0.77, 95% CI = 0.63-0.95; P = .01) in comparison with the placebo, the results were also confirmed by TSA. Conclusion: Among adult patients with septic shock, the use of low-dose hydrocortisone compared with control did not confer overall survival benefits, albeit improving shock reversal rate. The benefit of reducing 28-day mortality, ICU mortality, and hospital mortality was observed in combination use of hydrocortisone and fludrocortisone.